Monetary transmission under competing corporate finance regimes - Paul De Grauwe; Eddie Gerba (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
The behavioural agent-based framework of De Grauwe and Gerba (2015) is extended to allow for a counterfactual exercise on the role of banks for monetary transmissions. A bank-based corporate financing friction is introduced and the relative contribution of that friction to the effectiveness of monetary policy is evaluated. We find convincing evidence that the monetary transmission channel is stronger in the bank-based system compared to the market-based. Impulse responses to a monetary expansion are around the double of those in the market-based framework. The (asymmetric) effectiveness of monetary policy in counteracting busts is, on the other hand, relatively higher in the market-based model. The statistical fit of the bank-based behavioural model is also improved compared to the benchmark model. Lastly, we find that a market-based (bankbased) financing friction in a general equilibrium produces highly asymmetric (symmetric) distributions and more (less) pronounced business cycles.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E52; E44; E03; G21; G32; 330; monetary policy in the EA; monetary transmissions; banks; financial frictions; market based finance